Влияние высших гармоник тока на выбор токопроводов систем питания кранов - Андриенко, Петр Дмитриевич; Немыкина, Ольга Владимировна; Андриенко, Андрей Андреевич (Национальный технический университет "Харьковский политехнический институт", 2019)
В статье проведено исследование влияние высших гармоник тока на потери напряжения и мощности в токопроводах систем питания кранов. Получены необходимые расчетные соотношения для определения параметров токопроводов при наличии высших гармоник. На примере наиболее часто встречающихся частотно-регулируемых приводов показано, что в троллейных линиях из стальных уголков потери напряжения и мощности возрастают до 4 раз и до 1,43 раза, соответственно. Показано, что наличие нелинейной зависимости активного сопротивления стальных токопроводов от тока нагрузки и частоты приводит к увеличению расчетной величины потерь мощности по сравнению с расчетом через коэффициент искажения тока. Установлено, что величина tgφω1 может быть использована как конструктивный показатель токопровода. Наличие потерь мощности приводит к снижению КПД систем питания кранов до 7 %, что необходимо учитывать при выборе систем электропривода и его срока окупаемости.

To study the effect of high current harmonics on the power and voltage losses in the conductive lines of the crane power supply systems and the development of an account method for this influence inpractical calculations. Methodology. For research analytical methods and methods of simulation are used. Results.Analytical calculations have been performed for power losses and voltage losses for the conductors of crane power supply systems in the conditions of high harmonic gen-eration for frequency-controlled drives. Originality. For the first time, the authors have obtained the analytical expressions and graphical dependencies in relative units for practical calcula-tions that allow determining the effect of high harmonics to the values of power losses and voltage losses for crane supply sys-tems, while the parameters of steel conductors are nonlinear for load current and frequency. We have established that the values of power losses and voltage losses increase for crane power supply systems. It is shown thatthe power losses lead to a decrease the efficiencyof crane supply systems up to 7 %, which must be taken into account whenchoosing electric drive systems and its payback period. Practical value. The obtained theoretical expressions can be used for calculations, design, optimiza-tion of crane power supply systems in terms of high harmonic generation.
High current harmonics influence on the choice of conductors of crane power supply systems
Keywords: потери напряжения; потери мощности; стальные уголки; алюминиевые шины; voltage losses; power losses; steel materials; aluminum tires